-12x+2(x-5)+9=3x-10

Simple and best practice solution for -12x+2(x-5)+9=3x-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12x+2(x-5)+9=3x-10 equation:


Simplifying
-12x + 2(x + -5) + 9 = 3x + -10

Reorder the terms:
-12x + 2(-5 + x) + 9 = 3x + -10
-12x + (-5 * 2 + x * 2) + 9 = 3x + -10
-12x + (-10 + 2x) + 9 = 3x + -10

Reorder the terms:
-10 + 9 + -12x + 2x = 3x + -10

Combine like terms: -10 + 9 = -1
-1 + -12x + 2x = 3x + -10

Combine like terms: -12x + 2x = -10x
-1 + -10x = 3x + -10

Reorder the terms:
-1 + -10x = -10 + 3x

Solving
-1 + -10x = -10 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-1 + -10x + -3x = -10 + 3x + -3x

Combine like terms: -10x + -3x = -13x
-1 + -13x = -10 + 3x + -3x

Combine like terms: 3x + -3x = 0
-1 + -13x = -10 + 0
-1 + -13x = -10

Add '1' to each side of the equation.
-1 + 1 + -13x = -10 + 1

Combine like terms: -1 + 1 = 0
0 + -13x = -10 + 1
-13x = -10 + 1

Combine like terms: -10 + 1 = -9
-13x = -9

Divide each side by '-13'.
x = 0.6923076923

Simplifying
x = 0.6923076923

See similar equations:

| 25/8+35/6 | | 1/8+y=4 | | u^2-12u+36=0 | | 220=-6x^2-37x+65 | | 5x-(2x-5)=20 | | 62=-42 | | 18v^2-33vb+14b^2=0 | | 160-2x=34+24x | | 17(6c-1)-4=100c+17 | | 3x+22=2x-15 | | [x+4]=3x-5 | | 15x^2+29xy-14y^2=0 | | 45(6+7x)= | | 45(6+7x)=9 | | 2x+3(500-x)=1300 | | .5x+.5x+(x-15)+(x+25)=100 | | 3w-10=9+2W | | .18x=75 | | 5(x+4)-3x=10 | | 4w-12=-2w | | 18-1/22(2x)=9-1/22(x) | | .33x+(x-20)+(x-10)+40=360 | | -23-4=13-8x | | 4/9/8/15 | | 1+(7z-3)=7(-3+5)+2 | | 300=747+(-60) | | Y^2-12y=-31 | | 6x+15x^2=0 | | 5(4x+3)=21 | | -(3x-5)-(7x-6)+12=-3(x-1)-(12x+3)+3 | | 5/6+8/9 | | 5/6*12/17 |

Equations solver categories